TE'VÎLÂTÜ'L-KUR'ÂN BAĞLAMINDA MÂTÜRÎDÎ'DE HADİS YORUMU (KELÂMÎ HADİSLER ÖRNEĞİ) - YÜKSEL, FATİH MUHAMMET (Fırat Üniveristesi, 2019)
Hanefî ekolünün hadise karşı tutumu, klasik hadis anlayışına sahip bazı bilginler tarafından zaman zaman eleştirilmiştir. Ancak Hanefî mezhebinde hadisin konumunu görmek için özellikle kurucu imam Ebû Hanîfe'nin talebeleri Ebû Yûsuf ve Muhammed b. el-Hasen'in derlediği el-Âsâr isimli hadis/eser mecmuaları, çalışmalarıyla Hanefî ekolün hadisçi anlayışa yaklaşmasına yol açan Tahâvî'nin Şerhu Me'âni'l-Âsâr ve Şerhu Müşkili'l-Âsâr isimli eserleri göz ardı edilmemelidir. Semerkand Hanefîlerinin öncülerinden ve Ehl-i Sünnet kelâmının müessislerinden olan Ebû Mansûr el-Mâtürîdî'nin Te'vîlâtü'l-Kur'ân adıyla bilinen tefsir çalışması da Hanefî anlayışın zihin kodlarını bünyesinde barındıran eserlerden biri kabul edilebilir. Hanefîlerin hadisle alakalı görüşlerini ve hadis yorumlarını fıkıh kitaplarında bulmak mümkün olduğu gibi İmam Muhammed'in Mâlik b. Enes'ten yaptığı Muvatta' rivayeti gibi hadis çalışmalarından ve Te'vîlât gibi bazı tefsir çalışmalarından da tespit etmek mümkündür. Hadislerin sübutu, tashih ve taz'îfi gibi meselelerin hadis ilmi açısından önemi aşikârdır. Aynı öneme sahip olan diğer bir konu da hadislerin anlaşılması ve yorumlanmasıdır. Bundan dolayı mütekellim ve fakih olan Mâtürîdî'nin kelâmî hadisleri yorumlama biçimini irdelemek hem hadis yorumculuğu konusunda farklı bir anlayış sunmaya hem de Hanefîlerin hadis ve mana ehli oldukları yönündeki iddianın aydınlatılmasına katkı sağlayacaktır. Anahtar Kelimeler: Hadis, Yorum, Mâtürîdî, Kelâm, Te'vîlât, Hanefi

The attitude of the Hanafi school against the hadith has been criticized from time to time by some scholars having classical hadith understanding. However, in order to see the position of the hadith in the Hanafi school, especially the compilation hadiths / works called al-Asar of Abu Yusuf and Muhammad b. Al-Hasen who are the founder Abu Hanifa's students and Sharh Ma'ani al-Asar and Sharh Mushkil al-Asar of Tahawi who brought near Hanafi school to the hadithist approach, should not be ignored. The commentary work known as Ta'wilât al-Qur'an of Abu Mansur al-Maturidi who is one of the Semerkand Hanafi's pioneers and one of the founders of al-Sunnah Kalam, can be accepted as one of the works containing the mind codes of Hanafi conception. It is possible to find the Hanafi views and interpretations of the hadith in the books of fiqh, it is also possible to identify from the hadith studies such as Muwatta' narration made by Muhammad b. Al-Hasen and some exegesis studies such as Ta'wilât. The importance of issues such as being proved, revision, and taz'if of hadiths is evident in terms of hadith science. Another important issue is the understanding and interpretation of hadiths. Therefore, examining the manner of interpretation of the hadiths by Maturidi, who is mutakallim and fakih, will contribute both to providing a different understanding of hadith interpretation and to clarify the claim that the Hanafi people are the competent hadith and explanation. Key Words: Hadith, Interpretation, Maturidi, Kalam, Ta'wilât, Hanafi
Maturidi's hadith comment in the context of Ta'wilât Al-Qur'an (In the example of kalami hadiths)
Keywords: Din